An Enhanced Control Strategy for Mitigation of State-Transition Oscillation Phenomena in Grid-Forming Self-Synchronized Converter System with Islanded Power System - Ki Ryong Kim; Sangjung Lee; Jong-Pil Lee; Jaesik Kang (Energies, 2021)
This paper proposes an enhanced control strategy for mitigating state-transition oscillations in active and reactive power responses of self-synchronized converter system to secure the islanded power system stability. The self-synchronized converter is well known for “grid-forming” that is able to operate to stand-alone mode (SAM) providing grid voltage and frequency without phase synchronization units. Although the grid-forming (GFM) is self-synchronized, the inherent synchronization principle causes system degradation in which should maintain a point of common coupling (PCC) voltage for critical loads as well as transitions from grid-connected mode (GCM) to SAM and vice versa. Therefore, this paper focuses on resolving the inherent oscillatory issues in GFM self-synchronized converter system (especially adopted ‘synchronverter’ principle), and proposes a control strategy for controllability improvement based on stability analysis for smooth state-transition under islanded power system. The efficacy of the proposed control method is verified through a high-fidelity electromagnetic transient (EMT) simulation with case studies on 30kW synchronverter system and further experimental hardware-in-loop system (HILS) test with Opal-RT (OP-5707) platform.